Theorizing competition: An interdisciplinary framework - Carina Altreiter; Claudius Gräbner; Stephan Pühringer; Ana Rogojanu; Georg Wolfmayr (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2020)
This paper introduces a framework to facilitate an interdisciplinary analysis of 'competition'. While such an interdisciplinary analysis can be justified by referencing the various fields of social and economic life in which 'competition' is important, three challenges are found to aggravate such endeavor. To mitigate these challenges, and to explicate the often implicit meta-theoretical assumption in the scope, methodological and normative dimension, a meta-theoretical framework is proposed. Its usefulness is illustrated via a comparative description of selected contributions from the social sciences and humanities. Despite its limited scope, it yields some preliminary conjectures that may inspire future research: first, there are sufficient common elements across different concepts of competition that justify an interdisciplinary approach to study competition; second, apart from differences between disciplines, there are remarkable differences within disciplines that are at least of similar importance. Finally, there are important interdependencies between the meta-theoretical dimensions considered in the framework.
Keywords: B41; B5; P16; 330; competition; interdisciplinarity; methodology of the social sciences and humanities